Sūra-nirṇaya : Sūradāsa ke jīvana, grantha, siddhānta, aura kāvya kī nirṇayātmaka samīkshā - Parīkha, Dvārakādāsa (SAMP early 20th-century Indian books project, 1949)
On the life and works of Sūradāsa, 1483-1563, Hindi and Braj poet.